Capital management and wealth inequality - James Best; Keshav Dogra (Federal Reserve Bank of New York, 2023)
Wealthier individuals have stronger incentives to seek higher returns. We investigate theoretically the effect this has on long-run wealth inequality. Incorporating capital management into a standard RamseyCass-Koopmans model generates substantial long-run inequality: the majority of the population works and holds no capital, while a small minority holds a large amount of capital and manages it full-time. Counterintuitively, financial innovations or policies that reduce return differentials increase long-run wealth inequality. Egalitarian steady states may exist, but are inefficient and unstable: a small concentration in capital ownership causes a transition to an unequal steady state. Capital management introduces a novel equity-efficiency tradeoff: scale economies make it efficient for a few individuals to manage capital full-time, but under laissez-faire this generates substantial inequality. A utilitarian planner would instead instruct a few individuals to manage capital on behalf of society and transfer most of their income to the workers.
Keywords: D31; D83; E21; E22; G51; 330; wealth inequality; capital; returns; management; information; financial innovation